2019
DOI: 10.1038/s41371-019-0189-8
|View full text |Cite
|
Sign up to set email alerts
|

Fruit, vegetable intake and blood pressure trajectories in older age

Abstract: Diet rich in fruits and vegetables (F&V) is an established protective factor for hypertension, but the available evidence regarding the impact of F&V consumption on age-related blood pressure change is limited. We examined whether systolic (SBP) and diastolic (DBP) blood pressure trajectories are influenced by F&V intakes in an ageing Russian cohort. Dietary data was available for 8997 men and women in the Health, Alcohol and Psychosocial Factors in Eastern Europe prospective cohort study. Blood pressure measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Instead, most of the Russian surveys showed either continued increases with age or a plateauing or small decline in DBP from around age 50 years. This is consistent with the small longitudinal declines seen in DBP in the Russian HAPIEE study [ 34 ].…”
Section: Discussionsupporting
confidence: 89%
“…Instead, most of the Russian surveys showed either continued increases with age or a plateauing or small decline in DBP from around age 50 years. This is consistent with the small longitudinal declines seen in DBP in the Russian HAPIEE study [ 34 ].…”
Section: Discussionsupporting
confidence: 89%
“…Salt intake may have a large impact on BP trends and could have masked the association with fruit and vegetable intakes. 31 Numerous epidemiological, clinical, and experimental studies have linked dietary sodium intake to BP and have documented that a reduction in dietary salt intake can lower BP. 32 To a large extent agreeing with these results, we found that a higher salt intake was unfavorable for a healthy DBP trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…There is a plethora of recently published studies based on the ATHLOS dataset with promising results in several fields. Such fields include cardiovascular disease evaluation [13, 14, 15, 16, 17], demographic studies about sociodemographic indicators of health status [18] and the impact of socioeconomic status [19, 20, 21], nutrition science studies such as nutrition effects on health [22, 23, 24] and alcohol drinking patterns effects on health [25, 26] and even psychology studies assessing the impact of depression and other psycological disorders related to aging and health [27, 28, 29]. Nevertheless, the ATHLOS data specifications require analysis through Machine Learning methods to uncover the data complexity and better interpreting the characteristics that affect the state of human health.…”
Section: Introductionmentioning
confidence: 99%